1994
DOI: 10.1093/carcin/15.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Loss of gap junctions from DDT-treated rat liver epithelial cells

Abstract: The mechanism by which the liver tumor promoter 1,1-bis(p-chlorophenyl)-2,2,2-trichloroethane (DDT) inhibits gap junctional intercellular communication (GJIC) in WB-F344 rat liver epithelial cells could involve gap junction loss and/or decreased gap junction channel permeability. We examined these two possibilities in the present study. Immunohistochemical studies using antibodies specific to connexin43, the major gap junction protein expressed by these cells, revealed that gap junction number and size were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
6

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 25 publications
3
30
0
6
Order By: Relevance
“…The variation in results between the two methods may be due to several factors. First, Lucifer Yellow microinjection relies on visual detection under a microscope of dye transfer, 47 whereas the double dye technique utilizes the more sensitive detection of fluorescence by flow cytometry. 46,48 Indeed, the flow diagrams indicated that there was measurable but low transfer of calcein in both cell types.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The variation in results between the two methods may be due to several factors. First, Lucifer Yellow microinjection relies on visual detection under a microscope of dye transfer, 47 whereas the double dye technique utilizes the more sensitive detection of fluorescence by flow cytometry. 46,48 Indeed, the flow diagrams indicated that there was measurable but low transfer of calcein in both cell types.…”
Section: Discussionmentioning
confidence: 99%
“…30,33 In addition, a double dye flow cytometry technique was utilized to measure GJIC during the 24-h period of GCV incubation used in the bystander cytotoxicity experiment compared to the brief 10 min evaluation period used for Lucifer Yellow microinjection. [46][47][48] The results demonstrated that, although Lucifer Yellow microinjection suggested there was no GJIC in U251 cells expressing the DNCx43 and in HeLa cells, GJIC was observed by the double dye flow cytometry method. Further studies investigated the role of low GJIC on GCV phosphate transfer and bystander cytotoxicity.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations